Optimization of laser welding process parameters of stainless steel 316L using FEM, Kriging and NSGA-II. (September 2016) - Jiang, Ping; Wang, Chaochao; Zhou, Qi; Shao, Xinyu; Shu, Leshi; Li, Xiongbin
Highlights: Multi-objective laser welding process parameters optimization approach is proposed. The effects of process parameters on bead profile in light of Kriging are analyzed. Experiment results show the efficiency of the proposed approach. Abstract: Laser welding process parameters have significant effects on the welding bead profile and quality of the welding joint. This paper proposes an integration method of process parameters optimization using finite element method (FEM), Kriging metamodels and nondominated sorting genetic algorithm II (NSGA-II) in laser welding for stainless steel 316L. The process parameters in this study are laser power (LP), welding speed (WS) and laser focal position (LF). Firstly, a three-dimensional thermal finite element model is developed to obtain the simulated results of bead width (BW) and depth of penetration (DP). Then, Kriging metamodels are constructed to reflect the relationship between input process parameters and output responses. Finally, NSGA-II is used to search for multi-objective Pareto optimal solutions. In addition, the main effects and contribution rates of multiple process parameters on welding bead profile are analyzed. The results of verification experiments indicate that the optimal process parameters are effective and reliable for producing expected welding bead profile.